2011
DOI: 10.1002/ardp.201100335
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antioxidant and Antitumor Activity of Novel Pyridine, Chromene, Thiophene and Thiazole Derivatives

Abstract: 2-Tosylacetonitrile (1) when reacted with α,β-unsaturated nitriles 2a-c or a mixture of formaldehyde and 3-amino-2-substituted-pent-2-endinitriles 6a,b yielded pyridine derivatives 3a-c and 9a,b, respectively, while when subjected to react with salicylaldehyde yielded chromene derivatives 4 and 5, subsequently. The behavior of thiocarbamoyl derivative 10 derived from 1 towards some α-halogenated compounds have been investigated as well as its behavior towards elemental sulfur and phenyl isothiocyanate. Newly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 19 publications
0
36
0
1
Order By: Relevance
“…Literature reveals that chromenes and benzochromenes are an important chemical synthon, associated with a broad range of pharmacological activities such as antimicrobial [2][3][4][5], anticancer agent [6] hypolipidemic [7], antioxidant [8,9], analgesic [10], antileishmanial [11,12], vascular-disrupting activity [13], estrogenic anticoagulant and antispasmolytic [14], blood platelet antiaggregating [15] effects and activities. As part of our programmed aim to develop new methodologies for the preparation of 1H-benzo[f ]chromene derivatives [16][17][18], we have synthesized the title compound under microwave irradiation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reveals that chromenes and benzochromenes are an important chemical synthon, associated with a broad range of pharmacological activities such as antimicrobial [2][3][4][5], anticancer agent [6] hypolipidemic [7], antioxidant [8,9], analgesic [10], antileishmanial [11,12], vascular-disrupting activity [13], estrogenic anticoagulant and antispasmolytic [14], blood platelet antiaggregating [15] effects and activities. As part of our programmed aim to develop new methodologies for the preparation of 1H-benzo[f ]chromene derivatives [16][17][18], we have synthesized the title compound under microwave irradiation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Pyridine derivatives are also shown to possess significant DPPH radical scavenging activity [34,35]. Thus chemical synthesis of such derivatives has shown to possess better biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity of various thiophene derivatives has been reported in the literature and it has also been observed that compounds with high antioxidant activity served as antitumor agents [26]. The newly synthesized compounds reacted directly with nitric oxide and inhibited nitrite formation in an excellent way.…”
Section: Nitric Oxide (No) Scavenging Assaymentioning
confidence: 92%